Functional liquid crystalline epoxy networks and composites: from materials design to applications. (17th February 2022) - Li, Yuzhan; Ambrogi, Veronica; Cerruti, Pierfrancesco; Goswami, Monojoy; Yang, Zhou; Kessler, Michael R.; Rios, Orlando
ABSTRACT: Liquid crystalline epoxy networks (LCENs) are a class of materials that combine the useful benefits of both liquid crystals and epoxy networks exhibiting fascinating thermal, mechanical, and stimuli-responsive properties. They have emerged as a new platform for developing functional materials suitable for various applications, such as sensors, actuators, smart coatings and adhesives, tunable optical systems, and soft robotics. This article provides an overview of LCENs and their composites as functional materials, including their synthesis and characterisation, focusing on structure-processing–property relationships. We provide objective analyses on how materials engineers can use these relationships to develop LCENs with desired functionalities for targeted applications. Emerging areas, including advanced manufacturing and multi-functional design of LCENs are covered to show the overall progress in this field. We also survey the forward-looking status of LCEN research in designing novel materials for future technologies.